Analisis Pengaruh Kompetensi dan Kesejahteraan Karyawan Operasional Terhadap Utilisasi Fasilitas Bongkar Muat dan Dampaknya terhadap Produktivitas Terminal Peti Kemas Koja, Pelabuhan Tanjung Priok - Parhusip, Veronica; Bimarso, Wahyono; Sulam, Munyati; Rahardjo, Sri; Afra, Syeda Maria Ahmad (Institut Transportasi dan Logistik Trisakti, 2022)
The purpose of this research is to analyze the effect of competency and prosperity of employees on facility utilization and the impact on terminal productivity. Container terminal is the means of trade for in and out of goods at the port. provision of terminal facilities such as docks, stacking yards, pools for docking and also goods handling equipment for loading and unloading. KSO container terminal Koja is a subsidiary of PT. Pelabuhan Indonesia II and cooperation with PT Hutchison Port Indonesia. Koja terminal serves loading and unloading of goods both nationally and internationally and has a strategically important role in the growth of industry and trade as well as a business sector that contributes to national development. The research was conducted on operational employees by using quantitative methods technical path analysis. The result concluded that there is a direct influence on the utilization of facilities, the effect is significant. There is a direct influence of competence on terminal productivity, the effect is significant. There is a direct influence of facility utilization on terminal productivity, the effect is significant. There is a direct effect of welfare on terminal productivity, the effect is significant. There is an effect of total competence on the productivity of the terminal through the utilization of facilities and there is the effect of total welfare on the productivity of the terminal through the utilization of facilities.